Determining the dynamics of carbon monoxide formation during gas welding processes - Berezutskyi, Viacheslav; Khondak, Inna; Berezutska, Nataliia (Технологічний центр, 2021)
This paper reports a study of the air medium where welding processes take place, with special attention paid to the evolution of carbon monoxide (CO) in the working medium in the process of gas welding. Plots were constructed and polynomial dependences were obtained to show a change in the concentration of carbon monoxide in the air of the working area during gas welding. It was confirmed experimentally that the concentration of carbon monoxide exceeds the permissible sanitary and hygienic indicators MPC (20 mg/m3) during gas welding. As a result of the experiment, the effectiveness of the use of an additional device was proven, namely an umbrella gas concentrator, in order to capture welding gases that are formed during gas welding. It was established that the MPC is exceeded under certain working conditions and welding wire. The carbon monoxide formation during gas welding was analyzed; these processes were compared with electric arc welding. The mathematical dependences derived make it possible to assess the risks of the welders’ work and conclude that the electric arc welding is characterized by a much higher rate of CO evolution from the beginning of the welding process (8.5 mg/s), that speed then decreases over 20 s by 2 times (to 4.5 mg/s). In 90 s, the speed becomes constant, to 2 mg/s. In comparison, gas welding has almost the same rate of CO formation, namely 0.3–0.9 mg/s. By changing the types of welding wires used in gas welding and taking into consideration the type of material that needs to be welded (including the period of its use), it is possible to influence the volume of CO emissions entering the working area and an employee’s respiratory area.
Keywords: gas welding; analyzer-signaling device; carbon monoxide; harmful concentrations; gas poisoning